A Review on Phytoremediation of Crude Oil Spills - Yavari, S. (Kluwer Academic Publishers, 2015)
Changes in crude oil production and distribution have increased the incidence of oil spills throughout the world. Oil spills often cause destructive effects on aquatic and land ecosystems. The oil spill cleanup and recovery techniques are challenging and usually involve complex mechanical, chemical, and biological methods. Usually, mechanical removal of free oil is utilized as an effective strategy for cleanup in aquatic and terrestrial environments; however, they are expensive and need specialist personnel and equipment. The other commonly used method is the application of chemical materials such as dispersants, cleaners, demulsifiers, biosurfactants, and soil oxidizers. Nevertheless, these reagents can have potential harmful environmental impacts, which may limit their application. As an alternative, bioremediation can offer reduced environment risk; however, the limitations of microbial activity in the soil can make this option unsuitable. One area of bioremediation is phytoremediation, which offers potential for restoring large areas of contaminated ground. Plants are able to remove pollutants through processes such as biodegradation, phytovolatilization, accumulation, and metabolic transformation. This review presents the fate of crude oil spills in aquatic and land ecosystems and their environmental effects. Furthermore, the paper focuses on crude oil phytoremediation and its applications in polluted ecosystems. Â© 2015 Springer International Publishing Switzerland.